Efeitos de diferentes associações anestésicas em Tartaruga-da-Amazônia Podocnemis expansa Schweigger, 1812 (Testudines, Podocnemi-didae) criadas em cativeiro - Alves Júnior, José Roberto Ferreira (2006)
Chapter 2: Twenty Podocnemis expansa (Amazon river turtle), apparently healthy animals, weighting from 1.0 to 1.5 Kg, proceeding from a commercial bred farm in São José dos Bandeirantes district, Nova Crixás city, Goiás state, Brazil, was divided in two groups (G1, n=10 and G2, n=10). Each group received different protocol: G1 midazolam (2 mg/Kg IM) and ketamine (20 mg/Kg IM) and G2 - midazolam (2 mg/Kg IM) and ketamine (60 mg/Kg IM). The drugs were applied in left forelimb. After was observed the chelonians anesthetic parameters: environmental temperature, locomotion, muscular relation, pain stimulation on forelimbs and hind limbs, ability to manipulate and heartbeats were made at the times 0 and 5, 10, 20, 30, 45, 60, 90, 120, 150 and 180 minutes post injections. The G2 showed hight heartbeats and quickless and prolonged immobilization. The sedation obtained of those associations was good to realize chemical restrain to take blood samples and to accomplish anamnesis in Podocnemis expansa. Chapter 3: Twenty healthy Podocnemis expansa (Amazon river turtle), proceeding from a commercial captivity located in Araguapaz, Goiás, weighting from 1.0 to 1.5 Kg, were divided in two groups (G1, n=10 and G2, n=10). Group 1 (G1) received xylazine 1.5 mg/kg IM and propofol 5 mg/kg IV and group 2 (G2) xylazine 1.5 mg/kg and propofol 10 mg/kg IV. The drugs were applied in the left forelimb and in the cervical vertebral sinus, respectively. Assessments of the degree of sedation, coordination, ability to manipulate the animal, and response to a thoracic and pelvic painful stimulus were made. The anestheticals parameters were observed: coordination, muscular relation, right forelimb, hind limbs and tail painful stimulus, facility to manipulate and heartbeats as well environmental temperature. The sedation obtained by those associations were satisfactory, making possible pharmacological contention, sample biologic collection, physical examination and make small surgeries in this specimen. Statistic analysis indicated that the group 2 so efficient as group 1, in smaller dosage. Chapter 4: Twenty healthy Podocnemis expansa (Amazon river turtle), apparently healthy animals, weighting from 1.0 to 1.5 Kg, proceeding from a commercial bred farm in Araguapaz city, Goiás state, Brazil, was divided in two groups (G1, n=10 and G2, n=10). Group 1 (G1) received acepromazine 0.5 mg/kg IM and propofol 5 mg/kg IV and group 2 (G2) acepromazine 0.5 mg/kg and propofol 10 mg/kg IV. The drugs were applied in the left forelimb and in the cervical vertebral sinus, respectively. Assessments of the degree of sedation, coordination, ability to manipulate the animal, and response to a thoracic and pelvic painful stimulus were made. The anestheticals parameters were observed: coordination, muscular relation, forelimbs, hind limbs stimulus, facility to manipulate and heartbeats as well environmental temperature. The sedation obtained by those associations was satisfactory, making possible pharmacological contention, sample biologic collection, physical examination and make small surgeries in this specimen. Statistic analysis indicated that the G2 present effects prorogated.